Quality Of Public Services Of Bojonegoro District Government Through A Study Of Compliance Analysis On Public Service Standards, Indonesia - Suprastiyo, Ahmad (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
During 2021 to 2023, the level of compliance of the Bojonegoro Regency Government in the provision of public services has always increased from 2021 to 2023. In 2021, the fulfillment value of Bojonegoro Regency was 62.80 (yellow zone), in 2022 the fulfillment value of Bojonegoro Regency was 71.21 (yellow zone) there was a fairly small increase in value of 8.41 so that it was still in the yellow zone. Bojonegoro Regency in 2023 obtained a compliance level value of 86.80 (green zone) there was an increase in value of 15.59 from 2022. This study aims to realize the level of fulfillment of public service standards in improving the quality of service to the community. Qualitative research methods with data collection through interviews and document studies of regional secretariat reports and ombudsman reports, data analysis includes data collection, data condensation, data presentation, and conclusions. Research findings show that the level of public satisfaction with the Bojonegoro Regency Government is still in the moderate and good category with the average public satisfaction value in 2021 (95.50), 2022 (85.08), 2023 (87.82) still not in the very good category.